Nehru as a prophet of world peace - Kaur, Navtej (2008)
Jawahar Lal Nehru represented the best traits of an Indian which were tolerance, sagacity and love for peace. Nehru was an internationalist in his outlook. He developed his international outlook by keeping himself interested in the international problems. In his ideas he always cherished to have a world free of wars and nuclear threats, a world of oneness, of growth and development to better the lot of masses or humanity. The views of Nehru regarding world peace are important to the contemporary world because no country can be said to be really independent today. If there is any disaster in one country it may affect other countries in one way or the other. Similarly, the desire for peace is not confined to any one particular country; it is an aspiration of the entire world. The paper presents some of the views of Nehru in detail. - Reproduced.
Keywords: Nehru, Jawaharlal; Peace